Revocation of a Biological Father's Guardianship Rights Over His Child in the Context of Child Protection (Decision Study No. 329/Pdt.G/2020/PA.Bjb.) - Heriyani, Endang (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
Children are not yet able to fulfill their own needs. All of a child's needs must still be provided for by their parents, such as shelter, food, and clothing. In addition, children also need care, guidance, and education from their parents. A child's early education will determine their personality, mental state, and behavior in the future. In reality, many fathers as parents do not take care of their children, so it can be said that they have neglected their obligations. According to Article 49 paragraph (1) of Law Number 1 of 1974 concerning Marriage in conjunction with Article 109 of the Compilation of Islamic Law, the authority of one or both parents over their minor children can be revoked for a certain period of time if the parents seriously neglect their obligations towards their children or behave very badly. This study aims to determine the judge's considerations in revoking the biological father's guardianship rights over his child and appointing the grandfather as the child's guardian in decision number 329/Pdt.G/2020/PA.Bjb. The type of research used is normative legal research, which is research conducted by examining reference materials that constitute secondary data, also known as literature research. The data obtained in the literature research is secondary data, consisting of primary and secondary legal materials. The results of the research are analyzed prescriptively using the deductive method. The conclusions are: (1) The judge's consideration to revoke the biological father's guardianship rights over his child was because the biological father had neglected his obligations as a father and had abandoned his child when the child was 25 days old, and to date his whereabouts are unknown. The family has tried to locate the biological father but has been unsuccessful. (2) The judge's consideration in deciding that the plaintiff (grandfather) be appointed as the child's guardian is because the plaintiff has fulfilled the various requirements and conditions that must be met in the appointment of a guardian as stipulated in Article 4 paragraph (1) of Government Regulation Number 29 of 2019 concerning the Requirements and Procedures for Appointing a Guardian. The judge's decision to revoke the biological father's guardianship rights over his child and appoint the grandfather as the child's guardian can provide legal protection for the child, as the child is assured that his rights will be fulfilled.